EXPERIMENTAL AND NUMERICAL STUDY OF THE HEAT TRANSFER COEFFICIENTS OF DOUBLE PIPE HELICALLY COILED HEAT EXCHANGER - A. Hussain, Ammar; S. Golam, Ali (Journal of Engineering and Sustainable Development, 2016)
This work introduces an experimental and numerical study of the heat transfer coefficients of a double pipe helically coiled heat exchanger. It tested for both parallel and counter flow arrangements. Water is used as a working fluid on the inner tubes side and annulus tube side. The mass flow rate has range between (0.032-0.0721) kg/s for cold water while hot water is kept constant at (0.0724 kg/s). Also, the range of inlet temperatures of cold and hot water are (20-25°C), and (40-70°C), respectively. All experiments were performed at the Dean Number for annulus tubes side range of (1250-1700). The study was directed to focus on influencing the inlet mass flow rate of annulus tubes-side, and inlet temperatures of inner tubes-side over the effectiveness, axial temperature distribution of heat exchanger, efficiency, and heat transfer coefficient. All experimental data were performed under steady-state conditions. The results show that the mass flow rate ratio ((m.r) affects the axial temperature distribution of the heat exchanger also, the effectiveness and efficiency decreased by increasing the mass flow rate ratio. Likewise, comparisons between numerical and experimental results have been made. Empirical correlations between the Nusselt Number with Dean and Prandtl Numbers for the annulus tube have been found.